Humans, Other Animals and Disease: a comparative approach towards the development of a standardised recording protocol for animal palaeopathology - Stephanie Vann; Richard Thomas (Internet Archaeology, 2006)
In recent years the impact of animal disease on human societies has had an extremely high profile, with the spread of diseases such as Bovine Spongiform Encephalopathy (BSE) and foot and mouth among animal populations, as well as the transmission of diseases such as Human Immunodeficiency Virus (HIV), Ebola and Severe Acute Respiratory Syndrome (SARS) from animal to human populations. The social and economic impact of such illnesses has been profound. However, studies on the effect of animal disease in past human populations have been widely neglected. This is partly due to the inconsistent manner in which instances of animal disease (palaeopathology) are recorded, diagnosed and interpreted which, together with the typically low incidence of specimens per site, has precluded detailed studies of regional or temporal trends.